2012
DOI: 10.1371/journal.pone.0034047
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regulation of NR2B by Protein Phosphatase-1 for the Control of the NMDA Receptor in Neuroprotection

Abstract: An imbalance between pro-survival and pro-death pathways in brain cells can lead to neuronal cell death and neurodegeneration. While such imbalance is known to be associated with alterations in glutamatergic and Ca2+ signaling, the underlying mechanisms remain undefined. We identified the protein Ser/Thr phosphatase protein phosphatase-1 (PP1), an enzyme associated with glutamate receptors, as a key trigger of survival pathways that can prevent neuronal death and neurodegeneration in the adult hippocampus. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…; Farinelli et al . ) and may mediate the effect of CK1 inhibition, we determined whether PP1/PP2A is involved in the effect of CK1 inhibition on NMDAR activity in the PVN. Treatment of brain slices with tautomycetin (1 μ m , Tocris Bioscience, Bristol, UK), the specific PP1/2A inhibitor (Mitsuhashi et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Farinelli et al . ) and may mediate the effect of CK1 inhibition, we determined whether PP1/PP2A is involved in the effect of CK1 inhibition on NMDAR activity in the PVN. Treatment of brain slices with tautomycetin (1 μ m , Tocris Bioscience, Bristol, UK), the specific PP1/2A inhibitor (Mitsuhashi et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Farinelli et al . ), and PP1 targeting by neurabin and spinophilin is important for normal plasticity (Yan et al . ; Allen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Using yeast two‐hybrid screen and GST pull down assay, Ralf Enz revealed a direct association between PP1γ and glutamate receptor mGluR7b . Synaptic NMDA receptors recruit PP1α to mediated downstream aspects of synaptic signaling . The inhibition of PP1 results in a dysfunction in D(1A)DAR signal transmission in the prenatal cocaine‐exposed rabbit brain .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PP1γ‐mediated dephosphorylation of RIG‐I and MDA5 may also control the activation of NF‐κB . Moreover, studies revealed that neuronal receptors may directly recruit protein phosphatases, including PP1γ, to transmit downstream signals . These findings implicate an involvement of PP1γ in the regulation of cellular signaling and cancer cell physiology.…”
Section: Introductionmentioning
confidence: 98%